Orthodontic Management of Mesial Occlusion in Mixed Dentition Patients with Unilateral Cleft Lip and Palate - Akramovich, Yuldashev Temurkhon (Journal of Science in Medicine and Life, 2026)
The orthodontic management of mesial occlusion in patients with unilateral cleft lip and palate (UCLP) during the mixed dentition period presents distinct clinical challenges due to the complex craniofacial and dental disturbances associated with this congenital condition. UCLP commonly manifests with Class III malocclusion, maxillary transverse deficiency, delayed or ectopic tooth eruption, and dental arch asymmetry, all of which require carefully tailored orthodontic interventions during the critical developmental window of mixed dentition (approximately 6–12 years of age) to achieve optimal functional and esthetic outcomes. Beyond its anatomical implications, UCLP significantly affects oral functions such as mastication and speech and may also exert a negative psychosocial impact. Visible facial and dental discrepancies can influence self-esteem, social interaction, and overall psychological well-being in affected children. Orthodontic treatment in UCLP patients aims not only to correct dental malocclusions but also to facilitate proper maxillary alignment in preparation for subsequent surgical procedures, particularly alveolar bone grafting. Treatment protocols often incorporate early interceptive measures to address developing dental anomalies, followed by comprehensive orthodontic strategies designed to manage both skeletal and dentoalveolar discrepancies. Accurate assessment of craniofacial growth and dental development is essential for effective treatment planning. Diagnostic tools such as cephalometric analysis and radiographic imaging play a crucial role in formulating individualized orthodontic strategies that correspond with each patient’s unique growth pattern and developmental stage. Despite the documented benefits of early orthodontic intervention, determining the optimal timing and scope of treatment remains complex and highly dependent on cleft severity and associated dental anomalies. While several studies report favorable outcomes with early orthodontic management, others indicate limited effectiveness prior to surgical correction, underscoring the importance of continuous evaluation and personalized treatment planning.